2016
DOI: 10.4028/www.scientific.net/msf.858.418
|View full text |Cite
|
Sign up to set email alerts
|

Ion Implantation Defects in 4H-SiC DIMOSFET

Abstract: In this paper the influence of point defects generated by the ion implantation process in 4H-SiC DIMOSFET has been studied in detail. The point defects generated by the source or body implantation process have been detected by micro-photoluminescence and the effect of these defects on the electrical characteristics of the DIMOSFET has been studied. In particular it has been observed that a reduction of the source ion implanted dose produces a large reduction of point defects in the source region and a consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…All luminous intensity data was one-tenth of the original data to make sure the maximum luminous intensity was lower than 100 a.u. The native peak was 3.18 eV near to the SiC bandgap energy and the defect energy level was 2.56 eV which is near to the literature value [ 18 ]. From the literature, if the maximum luminous intensity is normalized to 100 a.u.…”
Section: Resultssupporting
confidence: 77%
“…All luminous intensity data was one-tenth of the original data to make sure the maximum luminous intensity was lower than 100 a.u. The native peak was 3.18 eV near to the SiC bandgap energy and the defect energy level was 2.56 eV which is near to the literature value [ 18 ]. From the literature, if the maximum luminous intensity is normalized to 100 a.u.…”
Section: Resultssupporting
confidence: 77%
“…These spectra show two peaks, a narrow one related to the 4H-SiC bandgap at 390 nm and another related to defects induced by ion implantation peaked at 488 nm and with a 175 nm full width half maximum (FWHM). The presence of the defect peak is associated with crystallographic damage, which introduces optically active intra-bandgap energy levels [3]. The intensity of this peak increases with increasing the temperature of the first annealing process; in particular, at 1750 °C its intensity is 7% higher than at 1650°C.…”
Section: Resultsmentioning
confidence: 99%
“…1,2) Despite these important improvements, several defects may still exist in grown films, mainly stacking faults (SF), dislocations, and pointlike defects either produced during the epitaxial growth or the implantation or etching process that may be required in device manufacturing. [3][4][5][6][7][8] The electrical behaviour of these defects impacts the overall quality of SiC devices, e.g., it has been shown that single Shockley stacking faults (SSSFs) act as recombination centers and expand during forward bias in bipolar devices, resulting in an increase in on-state resistance; 3) ð4; 4Þ SF can significantly scatter propagating electron waves, increasing both the resistance and the Schottky barrier in n-doped SiC films. 9) On the other hand, point defects, mainly Z 1=2 and EH 6=7 , induce a reduction in minority carrier lifetime and an increase in leakage current in Schottky diodes.…”
Section: Hmentioning
confidence: 99%